1962
DOI: 10.1037/h0040639
|View full text |Cite
|
Sign up to set email alerts
|

Altered adult behavior following chronic drug administration during infancy and prepuberty.

Abstract: That an altered environment during development can effect altered behavior during adulthood has been reliably shown for a variety of experimental conditions and behavioral dimensions (Bovard, 1958;Hebb, 1958). In this study 5s were administered drugs which could alter the magnitude of the stimulus input and the nature of the internal milieu. On the assumption that the manipulations were consistent with the postulated mechanisms of early-experience effects (cf. Berlyne, 1960;Meier, 1960), the 5s' adult behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…(3) The determination of whether stimulation of noradrenergic brain function in the neonatal rat would have carryover effects on adult behavior. Although a variety of pharinacologic agents administered during the infancy period have been shown to affect 242 SOBRIAN, WELTMAN, AND PAPPAS adult behavior (e.g., Hole, 1972;Lehtinen, Hyyppa, & Lampinen, 1972;Meier & Huff, 1962), previous research in this laboratory has indicated no carryover effect of neonatal amphetamine upon adult activity, open field, and passive avoidance behavior (Sobrian & Pappas, 1973) although adult brain norepinephrine levels were increased. These data indicate that biochemically immature brain tissue is sensitive to permanent alteration by d-amphetamine, although we were not able to detect behavioral consequences of this alteration.…”
mentioning
confidence: 95%
“…(3) The determination of whether stimulation of noradrenergic brain function in the neonatal rat would have carryover effects on adult behavior. Although a variety of pharinacologic agents administered during the infancy period have been shown to affect 242 SOBRIAN, WELTMAN, AND PAPPAS adult behavior (e.g., Hole, 1972;Lehtinen, Hyyppa, & Lampinen, 1972;Meier & Huff, 1962), previous research in this laboratory has indicated no carryover effect of neonatal amphetamine upon adult activity, open field, and passive avoidance behavior (Sobrian & Pappas, 1973) although adult brain norepinephrine levels were increased. These data indicate that biochemically immature brain tissue is sensitive to permanent alteration by d-amphetamine, although we were not able to detect behavioral consequences of this alteration.…”
mentioning
confidence: 95%
“…The genotype of the dog (terrier versus beagle) was also an important variable. Meier and Huff (1962) injected daily doses of reserpine, deanol, and saline for 40 days in neonatal rats. Later behavioral measures included the open-field test, Grice discrimination test, and the Lashley III maze.…”
Section: Psychoactive Chemicalsmentioning
confidence: 99%
“…There is, however, a relative paucity of information describing the effects of drugs, as a means of altering early experience, on adult behavioral patterns. That drug administration in infancy can have a marked influence on the behavior of mature organisms has been demonstrated by Meier and Huff (1962), Doty and Doty (1963), Heimstra and Sallee (1965), and recently by Gauron and Rowly (1968), andUehling (1969). These authors have shown that, in rats, early chronic administration of a variety of centrally acting drugs, e.g., chlorpromazine, reserpine, deanol, thioridazine, amphetamine, etc., leads to pronounced and persistent effects on many adult behaviors including degree of emotionality, dominance, discrimination, and adaptive problem-solving activities.…”
mentioning
confidence: 95%